Analysis and enlightenment on the cybersecurity strategy of various countries in the world - Yu-xiao LI; Yong-jiang XIE (网络与信息安全学报)
National cybersecurity strategy is the top-level design and strategic framework of the country, which in-cludes the national security, risk management and the personal protection. Now the main developed countries in the world have made the national cybersecurity strategy. So the strategy of our country drawing lessons from the ex-perience of the developed countries should also be enacted. And the strategy should include the cybersecurity situa-tion assessment, strategic target, strategic actions, the system and mechanism of internet governance, and so on.